Treatment of a Hopeless Tooth with Combined Endodontic-periodontal Lesion Using Guided Tissue Regeneration: A Case Report with One Year Follow-up - Khojaste, Moein; Navabi, Sara; Shiezadeh, Farid (Iranian Endodontic Journal, 2022)
Endodontic-periodontal lesions have always been a challenge for treatment due to the reduced success rate in comparison to endodontic or periodontal lesions alone. This case report describes surgical/endodontic management of supra-erupted non-vital maxillary incisor with primary periodontal and secondary endodontic lesions with mobility grade III and severe horizontal and vertical loss of attachment apparatus in a 55 years old woman with aggressive periodontitis. The successful results at one-year follow-up revealed that with an appropriate case selection strategy, proper regeneration method and soft tissue enhancement, severe combined endo-perio lesions may treat.